Anti-cancer potential of sea grape (Caulerpa racemosa) extract by altering epithelial-mesenchymal transition and pro-apoptosis proteins expression in MCF-7 breast cancer cells - Happy Kurnia Permatasari, Nasim Amar, Faqrizal Ria Qhabibi, Nur Iedha Tertiana, Anita Dominique Subali, Vincentinus Mario Yusuf, Dennis Ievan Hakim, Satrio Adi Nugroho, Wibi Riawan, Bambang Prijadi (Journal of Applied Pharmaceutical Science, 2024)
Breast cancer is a neoplasm that is increasing globally based on its prevalence. Caulerpa racemosa is a type of sea grape that has anti-cancer activity based on previous studies. We aim to determine the anti-cancer activity of C. racemosa extract on Michigan cancer foundation-7 (MCF-7) breast cancer cells through the mechanism of apoptosis by observing cell viability and caspase-3 expression, also as an anti-metastatic agent on expression of Snail and Vimentin. A true experimental study was carried out using a randomized post-test-only control group design. MCF-7 cells were used as subjects with the intervention of C. racemosa extract at varying doses. Cell apoptotic was assessed by flow cytometry and cell viability test, while anti-metastatic activity was assessed by wound healing assay. Immunofluorescence staining was used to assess the expression level of caspase-3, Snail, and Vimentin. The results showed an increased activity of cell apoptosis, according to flow cytometry and cell viability tests. Furthermore, expression of caspase-3 was found to be significantly higher in the 400 g/ml dose group and MCF-7 cell migration inhibition by decreasing Snail and Vimentin protein expression. These results indicate a “novel mechanism” of C. racemosa in the MCF-7 model as an anti-cancer and anti-metastatic agent to inhibit breast cancer progression.
Keywords: Apoptosis, caspase 3, Caulerpa racemosa, epithelial-mesenchymal transition (EMT), Snail, Vimentin